THE PROTOTYPE APPROACH TO TEACHING THE NEGATIVE PREFIXES DE- AND UN- TO KURDISH EFL STUDENTS - HAMAWAND, ZEKI SABER; HUSSIEN, RAMAN QALANDAR (Journal of Duhok University, 2023)
comparing two pedagogical models: traditional and modern. The traditional model relies on form-focused repetition, while the modern model, inspired by Cognitive Grammar, adopts a meaning-oriented approach, emphasizing the coherent category formed by various senses of a linguistic unit. The study highlights the significance of polysemy in grammar instruction, arguing that a negative prefix encompasses multiple senses beyond its morphological function. The study utilized an online-based classroom for both treatments, employing three tests and a questionnaire as data collection tools. The research concludes that the cognitive meaning-based approach proves more effective than the traditional form-focused method in teaching the selected negative prefixes. Furthermore, the study demonstrates the successful application of this approach in an online setting, as indicated by the questionnaire responses